DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases - Wielscher, Matthias; Mandaviya, Pooja R.; Kuehnel, Brigitte; Joehanes, Roby; Mustafa, Rima; Robinson, Oliver; Zhang, Yan; Bodinier, Barbara; Walton, Esther; Mishra, Pashupati P.; Schlosser, Pascal; Wilson, Rory; et al. (Nature communications, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD. Chronic inflammation, marked by C-reactive protein, has been associated with changes in methylation, but the causal relationship is unclear. Here, the authors perform a Epigenome-wide association meta-analysis for C-reactive protein levels and find that these methylation changes are likely the consequence of inflammation and could contribute to disease.